The performance of the complicated dental surgeon in tolerant sinuses of odontogenic origin (Research, Society and Development, 2023)
The objective of this study is to present how the dental surgeon should act in the treatment of sinus infections of odontogenic origin from diagnosis to treatment. The present work refers to a narrative review of the literature, in which the bibliographic searches were based on the selection of articles published in the languages: Portuguese and English that were available in the electronic databases: PubMed, Lilacs, Google Scholar and Scielo , between the years 2006 to 2021.Based on reading, the review was attributed to clinical studies, case reports and gray literature (monographs, theses and dissertations), which were relevant to the theme. It is concluded that the diagnosis is crucial and essential for the choice of intervention to be performed by the professional, moreover it is important to understand that this condition is caused by dental infections and therefore requires a different treatment approach from common sinusitis. An accurate diagnosis and effective treatment can help alleviate symptoms and prevent complications. In addition, it is essential to maintain good oral hygiene and regularly consult a dentist to prevent the occurrence of dental infections that can lead to odontogenic sinusitis.